STRES SEKOLAH DAN STRATEGI PENANGGULANGANNYA (TINJAUAN PSIKOLOGI PENDIDIKAN) - Sakdiah, Halimatus (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
The quality and the excellent ofan education is a hope and a step to reach in order to make come true the national education goal, especially in creating the quality and the competitively hutnan resources. But, subcorlsciously, the educational program developed by the government and private through the quality of school education institution had a high dcrnand and hope toward their student as their school label. A higher demand and hope may affect a stress for the studcnt, and so it needs a scrious treatment irt older tlu: quality o[ education as thc goal did not impact in contrary' ]'hcrc{brc, t.his writing purposely to discuss about school strcss and thc stratcgy to solution for it.